Plasmodium vivax infection-driven modulation of sterol carrier protein reveals a metabolic link to reproductive physiology in Anopheles stephensi - Kumari, Seena; Yadav, Pooja; Sankhala, Nirmala; Rani, Jyoti; Sharma, Gunjan; Chauhan, Charu; Tevatiya, Sanjay; Dixit, Rajnikant (Frontiers in Immunology, 2025)
Mosquitoes rely exclusively on blood-derived sterols, transported by sterol carrier protein (SCP), for reproduction and metabolic regulation. SCP expression is strongly induced after blood feeding and dynamically modulated during Plasmodium vivax infection—upregulated in the midgut and salivary glands but suppressed in hemocytes—indicating that parasite infection modulates the host sterol transport and metabolism. RNAi-mediated knockdown of SCP significantly reduced mosquito fecundity, underscoring its vital role in reproductive physiology. These findings highlight SCP as a key metabolic regulator linking nutrient uptake to reproductive outcome, while its Plasmodium infection-driven modulation may facilitate the parasite growth. While reproduction remains the primary physiological outcome, the metabolic modulation of SCP during infection also points to it as a possible transmission-blocking target in integrated malaria control strategies.